A systematic mapping of public health primary prevention interventions with relevance for policing - Sondhi, Arun (International journal of police science & management, 2023)
This study aimed to utilise systematic mapping techniques to assess existing empirical reviews of the evidence-base for primary prevention public health initiatives relevant to policing. In total, 9410 records were extracted of which 9373 were screened by two researchers; 356 studies were assessed for eligibility of which 134 titles were included. The majority of titles were academic publications (81%) across 16 subject domains. The main domains reviewed were violence (53%), substance misuse (37%) and mental health (27%). Forty-two per cent of the titles were across multiple points of contact and 38% were within school settings. Few primary prevention studies were delivered for domestic abuse, female genital mutilation, hate crime, road traffic accidents, terrorism and white-collar crimes. Positive outcomes were ascribed to parenting, family-based, school and pre-school primary prevention interventions. Definitional problems identifying primary prevention initiatives from the literature were identified as a major concern. Thematic analysis identified issues linking causal mechanisms with behaviour change and how to ensure high-quality methods are deployed to measure outcomes. Further work is required to develop preventative approaches in areas with limited knowledge. It is recommended that research focuses on expanding understanding causal mechanisms underpinning primary prevention initiatives.